Contributions to the Flora of Myanmar V: a new record of Mallotus tokiae (Euphorbiaceae) with the description of flower morphology from Lampi Island - Toyama, Hironori; Aung, Mu Mu; Tagane, Shuichiro; Naiki, Akiyo; Suddee, Somran; Nagamasu, Hidetoshi; Nagahama, Ai; Win, Swe Swe; Tanaka, Nobuyuki; Yahara, Tetsukazu (Thai Forest Bulletin (Botany), 2020)
Mallotus tokiae (Euphorbiaceae), a poorly known species, was described based upon a single fruiting specimen from Surat Thani Province, peninsular Thailand. We found this species with staminate and slightly mature pistillate flowers in Lampi Island, Myanmar. A new locality record, description of flowers, preliminary conservation assessment and DNA barcoding of this species are provided.